HISTOPLASMOSIS IN NON-HIV IMMUNOCOMPROMISED PATIENT RESIDING IN A NON-ENDEMIC AREA IN BRAZIL - Siqueira Gonçalves, Thatyana; Pazinato Ritter, Laura; Fraga Guimarães, Taiguara; Silva de Miranda Godoy, Cássia; de Bastos Ascenço Soares, Renata (Revista Unimontes Científica, 2021)
Introduction: Histoplasmosis is a fungal disease, caused by Histoplasma capsulatum. Goal: To report a case of an immunocompromised patient with diagnosis of histoplasmosis in a non-endemic region. Methodology: Case report. Case report: Patient carrier of rheumatoid arthritis, makes continuous use of methotrexate and has reported contact with large amount of bat guano. Result of cervical lymph node culture was positive for H. capsulatum. Discussion: The infection was presented related to drug-induced immunosuppression in a non-endemic area. Conclusion: In view of the location where the infection occurred, the geographic expansion of the disease and the importance of this report for the literature are clear.